2005
DOI: 10.1530/rep.1.00663
|View full text |Cite
|
Sign up to set email alerts
|

An update of the pathophysiology of human gonadotrophin subunit and receptor gene mutations and polymorphisms

Abstract: New information about mutations and polymorphisms in the genes for the gonadotrophins and their receptors has become available in the last few years. In this short review mutations and polymorphisms in gonadotrophins, their receptors and their patho-physiological effects and implications are discussed. An increasingly clear picture about the structure -function relationships of gonadotrophin action is emerging from the combining the types and the locations of the mutations with their phenotypic effects and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 98 publications
2
91
1
Order By: Relevance
“…Exon 10 of canonical FSHR1 has remained the main target to search for mutations leading to POF and cancer. As mentioned earlier, till date, only few naturally occurring mutations have been reported for FSHR compared with almost 30 described for LHR (Themmen & Huhtaniemi 2000, Themmen 2005), although FSH is a key player controlling these processes. Siegel et al (2013) provided an exhaustive review on the molecular basis of FSH action, including an update on mutations reported on FSHR.…”
Section: R37mentioning
confidence: 99%
See 1 more Smart Citation
“…Exon 10 of canonical FSHR1 has remained the main target to search for mutations leading to POF and cancer. As mentioned earlier, till date, only few naturally occurring mutations have been reported for FSHR compared with almost 30 described for LHR (Themmen & Huhtaniemi 2000, Themmen 2005), although FSH is a key player controlling these processes. Siegel et al (2013) provided an exhaustive review on the molecular basis of FSH action, including an update on mutations reported on FSHR.…”
Section: R37mentioning
confidence: 99%
“…Besides ovarian cancers, elevated levels of FSH are also associated with premature ovarian failure (POF), resistant ovarian syndrome (ROS), and PCOS, and intense efforts have been undertaken to detect naturally occurring mutations in FSHR associated with these clinical conditions. Natural mutations detected in FSHR are relatively low compared with LH and thyroid-stimulating hormone (TSH) receptors (Themmen & Huhtaniemi 2000, Meduri et al 2003, Themmen 2005, Huhtaniemi & Themmen 2005. Mutations in FSHR appear to be a very rare cause of PCOS, POF, and primary to early secondary amenorrhea combined with arrested follicular maturation and anovulatory infertility.…”
Section: Introductionmentioning
confidence: 99%
“…The Authors have also persistently and systematically followed the single patient, and received consent from family members. Although mutations in gonadotropins/gonadotropin receptors are considered rare [19,20,24,25], the Authors have gone on to demonstrate that both the LHCGR alleles are "hit" with two different mutations in heterozygous condition, an event considered even more rare. Moreover, in the present study they also identified a novel mutation in exon I in the signal peptide encoding sequence that had never previously been reported.…”
Section: Final Remarks and Future Directionsmentioning
confidence: 99%
“…Although initially considered rare, in the past two decades, various mutations and polymorphisms have been identified in the human LHCGR (located on chromosome 2) that consists of 11 exons and 10 introns [18][19][20][21][22][23]. These include unique SNPs, or deletions, or point mutations identified throughout the LHCGR resulting in a spectrum of fertility/infertility phenotypes including sex reversal [18][19][20][21][22][23]. In this issue of JARG, Mitri et al, report a novel compound heterozygous mutation in the LHCGR and present interesting clinical phenotypes that manifest in the affected female patient (Mitri et al, A novel compound heterozygous mutation of the luteinizing hormone receptor: implications for fertility, doi:10.1007/s10815-014-0249-5).…”
mentioning
confidence: 99%
“…The first review (Themmen 2005) summarises the current knowledge about the mutations and polymorphisms detected in the human gonadotrophin subunit and receptor genes. Although the phenotypes of most of the possible activating and inactivating mutations of these genes are reasonably well known by now, gaps still exist in our knowledge.…”
mentioning
confidence: 99%